The role of lichen communities in superficial deterioration of their rock substrates: studies of the lichen-rock interface of two historical buildings in the City of Guanajuato, Mexico - Puy-Alquiza, Maria Jesús; Gómez Peralta, Marlene; Miranda-Avilés, Raúl; Reyes-Zamudio, Veridiana; Salazar-Hernández, Ma. del Carmen; Ordaz Zubia, Velia Yolanda (Acta Universitaria, 2015)
In this paper we present the deterioration processes that exert lichen communities in siliceous sandstones of two historical monuments of the nineteenth and twentieth Centuries of the Guanajuato city (steps of the Guanajuato University and the School of Music at the Guanajuato University). In addition to contributing to the knowledge of deterioration, data on the lichen species found, is provided, the causes of its growth and its role in the deterioration of the stone material, in order to implement measures of protection and prevention. The lichen-rock interface was observed using complementary techniques such as, optical microscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), Inductively Coupled Plasma) (ICP), and energy dispersive spectroscopy X-ray (EDS). Were identified five species of lichens: Xanthoparmelia mexicana, Xanthoparmelia tasmanica; Caloplaca aff. brouardii, Caloplaca aff. ludificans and Aspicilia sp. These lichens penetrate 0.5 µm to 50 µm on the substrate through its rhizines, causing disintegration of minerals in the rock surface (plagioclase, quartz and feldspar). The disintegration of minerals along with the changes in chemical composition in the lichen-rock interface shows a negative action on the rocky surface, (the decrease in SiO2, Al2O3, Zn, and K2O and the presence of a high percentage in CaO, Fe2O3, and MgO).
Keywords: Array; Array; Array; Array